(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The poisson queuing model indicates the distribution of interval arrival time and services time is exponentially distributed based on the First-comeFirst-serve (FCFS) and the Laplace transforms analyze the various probability generating function. Finally, the steady state solutioninvestigated for the better performance and uses for queuing model on the basis of Kendall‟s notation.